Comparison of Slalom Dribble and Chain Dribble Training on Improving Dribble Skills in High School Students - Irfan; Sabar, Muhammad Sardi; Suwardi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research aims to determine the increase in slalom dribble and relay dribble training and to compare the effectiveness of these training methods in improving the dribble skills of the men's basketball team at Public High School 1 Pangkep. This research is experimental. In this study, the sample consisted of 16 male students who were active in extracurricular basketball. The dribble test and measurement research instrument used is the AAHPERD Basketball Control Dribble Test Data. The data were analyzed using the inferential statistics t-test. The results of this study show that: (1) there is an influence of slalom dribble training on improving ball dribble skills on the men's basketball team at Public High School 1 Pangkep; (2) there is an influence of relay dribble training on improving ball dribble skills on the men's basketball team at Public High School 1 Pangkep; and (3) there is a comparison between slalom dribble training and relay dribble training in improving ball dribble skills on the men's basketball team at Public High School 1 Pangkep.